Case Study Review from Indonesia and Finland: The implementation of Indonesian government program called “The Independent Learning, Independent Collage.” - Hartadi Hartadi; Rudy Handoko; Rachmawati Novaria (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The emergence of having a good education system is one of the hot issues among scholars and stakeholders. Indonesia is now facing various challenges to create a good education system for the better future of its people. This paper examines the problems of Indonesia's education system. A qualitative descriptive research design was applied for the present study. The data in the present study were obtained through observation, library, and documentation study, as well as make use of state of the art sources in the related studies both education in Indonesia and Finland as a role model. Furthermore, the literature review was used to elucidate the findings from the previous studies. The data were analyzed qualitatively by mapping and describing the problems of Indonesia’s education system and take a look at the similar aspects of the Finland system. It discusses Indonesia’s education problems, including well-trained teacher’s deployment, student’s tuition fee, class size, and school facilities and access, then further explores Finland's success story in the educational sector as a role model. Mapping the problems of Education in Indonesia enables us to improve Indonesia's education system to achieve international competitiveness in 2025.